Effects of Macrobiota on the Transfer Efficiency of Essential Elements and Fatty Acids From Phytoplankton to Zooplankton Under Eutrophic Conditions - Feniova, Irina Yu; Karpowicz, Maciej; Gladyshev, Michail I.; Sushchik, Nadezhda N.; Petrosyan, Varos G.; Sakharova, Ekaterina G.; Dzialowski, Andrew R. (Frontiers in Environmental Science, 2021)
The transfer pathways of organic matter and elements from phytoplankton to zooplankton in freshwater ecosystems are important for understanding how aquatic ecosystems function. We conducted a mesocosm experiments to determine how fish and zebra mussels altered the transfer efficiencies of essential substances including carbon (C), polyunsaturated fatty acids(PUFAs), total fatty acids (FAs), phosphorus (P) and nitrogen (N) from phytoplankton to zooplankton. We assessed the transfer efficiencies of the essential substances from phytoplankton to zooplankton as the ratio of their zooplankton production (P) per unit of biomass (B) to that of phytoplankton to exclude grazing or predation effects. We hypothesized that zebra mussels and fish would affect the transfer of materials from phytoplankton to zooplankton by altering contents of essential elements and FAs in phytoplankton and zooplankton communities and/or due to shifts in planktonic community structure mediated by grazing and/or predation. Fish increased the transfer efficiencies of eicosapentaenoic acid 20:5 ω-3 (EPA), docosahexaenoic acid 22:6 ω-3 (DHA) and P relative to the control. We speculate that fish weakened the control of zooplankton over algal assemblage by selectively feeding on larger cladocerans such as Daphnia. Therefore, fish can increase the relative proportion of high quality food for zooplankton, improving food conditions for available zooplankton. In contrast, zebra mussels reduced the transfer efficiencies of EPA and DHA relative to the control likely due competition with zooplankton for PUFA-rich food particles. However, zebra mussels did not have any impact on the transfer efficiencies of C, total FAs, N and P. EPA, DHA, and P were transferred more efficiently than C from phytoplankton to zooplankton, while total FAs, which are commonly used as an energetic source, were transferred as efficiently asC . Enrichment of consumers with the most important substances relative to their basal food sources creates the potential for the successful transport of these substances across aquatic trophic webs.